PENGADAAN WALIMATUL ‘URSY DI MASA PANDEMI DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM NEGARA - Nur Azizah, Alfinna Ikke (Fakultas Syariah - IAI Al-Qolam Malang, 2020)
Walimatul 'ursy is a wedding party, this walimatul' ursy aims to inform the public that wedding activities will be carried out. In the invited walimatul ‘ursy, usually the family of both parties of the bride and groom, neighbors and closest friends. However, this year we are being tested by the one and only God, Allah SWT., With the presence of the coronavirus. This virus has an impact on the fields of education, economy, health and the practice of worship. One of the impacts on the implementation of worship is on the issue of marriage, many people are confused about whether to hold walimatul ‘ursy / wedding party or not. Therefore, the writer feels the need to study and examine the current conditions regarding the implementation of walimatul 'ursy. The method used in this research is a qualitative method. The results of this study are as follows, according to Islamic law walimatul ‘ursy during a pandemic should not be done because it is to prevent congestion or damage based on the rules of ushul fiqh which means